More students doing more maths? Student attitudes to mathematics and perceptions of its teaching in a new post-compulsory course. (23rd July 2020) - Homer, Matt; Mathieson, Rachel; Tasara, Innocent; Banner, Indira
Abstract: In England, a relatively new set of post-16 qualifications has been developed under the umbrella term 'Core Maths', with a focus on the application of mathematics in context, including the kinds of mathematics needed to support other subjects, to provide a sound basis for the mathematical demands of higher education and employment and to develop problem-solving skills for use in life. The UK government has an ambition that all post-16 students should be studying some mathematics, and Core Maths was designed in part with this aspiration in mind. In this paper, longitudinal questionnaire data from over 100 Core Maths students in 13 case study institutions are analysed to measure students' views of teaching as transmissionist, their mathematical dispositions and self-identification and how these change over a year of studying Core Maths. We find some evidence that pedagogy in lessons is perceived as being less transmissionist than it was in school mathematics pre-16. There is also some evidence of a negative change in students' mathematical dispositions over a year of Core Maths. We conclude that supporting teachers in embedding new pedagogical approaches remains a challenge and that this issue could inhibit the growth of new qualifications like Core Maths.